A study on factors that influence employees' intention to stay at The Semi Government Organization In Kuantan, Pahang / Ili Syamimi Hapiz and Siti Khatijah Senan - Hapiz, Ili Syamimi; Senan, Siti Khatijah (2014)
The organization cannot be generated efficiently without valuable employees, revenue and accomplishment. High salary and pleasant working conditions cannot be promise as employees stay in the organization. So, most of the Human Resources Department needs to have some targeted to achieve and they need to explore the factors employees stay with the organization. There are more other factors that influence employees' intention to stay in the organization. The industry is healthier than others industry when they have less employees' turnover in the organization. The research problem carried out in this study is to observe the impact of training and development, career development, compensation and benefits, job satisfaction, performance appraisal and achievement, and organizational commitment with employees' intention to stay in semi government, at Kuantan, Pahang. This research will investigate the main factor influencing employees' retention and why employees are preferred to stay in the semi government organization. The results indicate that the factors positively correlated with employees' intention to stay. The findings and recommendations were also addressed.